STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN MINAT NASABAH PEMBIAYAAN PENSIUNAN DI BSI KCP PASAR BABAT LAMONGAN - Austinnisa', Fadia; Ardyansyah, Farid (Jurnal Ekonomika dan Bisnis Islam, 2023)
This study aims to analyze the sharia marketing strategy applied at BSI KCP Pasar Babat Lamongan in increasing the interest of pension financing customers in 2022 which had decreased. This research uses qualitative methods with data collection techniques that include observation, interviews and documentation. The informants selected in this study are determined by purposive sampling techniques, namely by choosing sources that are considered to know the research topic best. Data analysis uses descriptive analysis, referring to the concept of marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) which is reviewed through the value of sharia marketing from the nature of the Prophet SAW (Shiddiq, Fathanah, Amanah, Tabligh). The results of the study stated that the sharia marketing strategy that implements a marketing mix combined with the exemplary qualities of the Prophet SAW, was able to increase the interest and number of disbursements of pension financing customers in November 2022.